2012
DOI: 10.1007/s00439-012-1181-3
|View full text |Cite
|
Sign up to set email alerts
|

Traditional and targeted exome sequencing reveals common, rare and novel functional deleterious variants in RET-signaling complex in a cohort of living US patients with urinary tract malformations

Abstract: Signaling by the glial cell line-derived neurotrophic factor (GDNF)-RET receptor tyrosine kinase and SPRY1, a RET repressor, is essential for early urinary tract development. Individual or a combination of GDNF, RET and SPRY1 mutant alleles in mice cause renal malformations reminiscent of congenital anomalies of the kidney or urinary tract (CAKUT) in humans and distinct from renal agenesis phenotype in complete GDNF or RET null mice. We sequenced GDNF, SPRY1 and RET in 122 unrelated living CAKUT patients to di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
58
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 83 publications
(61 citation statements)
references
References 41 publications
2
58
0
1
Order By: Relevance
“…Patients with CAKUT have mutations in the RET/GDNF signaling pathway [ 13 -16 ]. A study of 122 patients with CAKUT identifi ed heterozygous deleterious sequence variants in GDNF or RET in 6/122 patients, 5 %, while another group screened 749 families from all over the world and identifi ed three families with heterozygous mutations in RET [ 13 ]. Similar fi ndings have been reported in studies of fetuses with bilateral or unilateral renal agenesis [ 14 , 16 ].…”
Section: Embryologic Mechanismssupporting
confidence: 55%
“…Patients with CAKUT have mutations in the RET/GDNF signaling pathway [ 13 -16 ]. A study of 122 patients with CAKUT identifi ed heterozygous deleterious sequence variants in GDNF or RET in 6/122 patients, 5 %, while another group screened 749 families from all over the world and identifi ed three families with heterozygous mutations in RET [ 13 ]. Similar fi ndings have been reported in studies of fetuses with bilateral or unilateral renal agenesis [ 14 , 16 ].…”
Section: Embryologic Mechanismssupporting
confidence: 55%
“…Analysis of multiple genes in parallel using NGS in patients with CAKUT has demonstrated that <10% patients with isolated CAKUT carry variants in previously implicated genes, such as HNF1B, PAX2, EYA1, SIX5, and RET. 23,24,37 This finding implies that the majority of causes of CAKUT are still unknown. Meanwhile, the list of novel variants requiring functional charac terization to determine whether they are true risk factors or harmless polymorphisms has expanded.…”
Section: Targeted Next-generation Sequencingmentioning
confidence: 92%
“…Since then, mutations in several genes, including GDNF [7], RET [8], HNF1B [9], SALL1 [10], SIX5 [11], BMP4 [12], GREM1 [13], FRAS1 , and FREM2 [13,14], have been identified as causing URA. All of these genes are involved in crucial signaling during nephrogenesis, and the majority show an autosomal dominant (AD) mode of inheritance.…”
Section: Introductionmentioning
confidence: 99%